2019
DOI: 10.3390/pr8010016
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Fibrex Gel by Fungal Laccase: Gel Rheological and Structural Characteristics

Abstract: Sugar beet fibre (fibrex) is an abundant side-stream from the sugar refining industry. A self-produced laccase from Funalia trogii (LccFtr) (0.05 U/µg FA) successfully cross-linked fibrex to an edible gel. Dynamic oscillation measurements of the 10% fibrex gels showed a storage modulus of 5.52 kPa and loss factors ≤ 0.36 in the range from 20 to 80 Hz. Comparing storage stability of sweetened 10% fibrex gels with sweetened commercial 6% gelatin gels (10% and 30% d-sucrose) indicated a constant storage modulus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
1
12
0
1
Order By: Relevance
“…As a result, the storage modulus of sweetened cross-linked fibrex gels formed with LccFtr stayed stable for over a month of storage after the above-mentioned heat treatment. Due to their highly similar chemical structure, these results should be transferable to the AX gels in this study [47].…”
Section: Storage Stability Of Arabinoxylan Gelsmentioning
confidence: 72%
See 2 more Smart Citations
“…As a result, the storage modulus of sweetened cross-linked fibrex gels formed with LccFtr stayed stable for over a month of storage after the above-mentioned heat treatment. Due to their highly similar chemical structure, these results should be transferable to the AX gels in this study [47].…”
Section: Storage Stability Of Arabinoxylan Gelsmentioning
confidence: 72%
“…AX gels formed with LccPpu were analyzed with LCMS/MS, and 8-O-4 dehydrodimers of ferulic acid were detected as cross-links. Dominating dimers of ferulic acids in cross-linked wheat bran AX were 8-O-4 and 8-5 , both of which increased after gel formation [44,47]. It was recently reported that in the cross-linked gels, which were formed with LccFtr, 8-5 dimers of ferulic acids were predominant [47].…”
Section: Identifying Diferulic Acids In Cross-linked Arabinoxylan Gelmentioning
confidence: 88%
See 1 more Smart Citation
“…It is well documented that 8-5′ and 8- O -4′ di-FA are the major isomers formed after oxidation reactions of FA monomers in ferulated polysaccharides [ 35 ]. Indeed, in nature, the major dehydrodimers are 8- O -4′ and 8-5′ for most angiosperm tissues, but abundant dimer isomers are also found in ferulated polysaccharide gels prepared under controlled conditions [ 36 , 37 ]. Just a small amount of tri-AF was formed in the microbeads after 120 min of laccase exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Neutral sugar composition was performed by gas chromatography [ 42 ] (PerkinElmer, Clarus 580) using a high-performance capillary column (Elite 225, PerkinElmer, 30 mL × 0.32 mm ID × 0.15 µm film thickness). FA and its dimers and trimer content were analyzed by HPLC [ 36 ] using an Alltima C18 column (250 × 4.6 mm; Alltech Associates, Deerfield, IL, USA) and a photodiode array detector, Waters 996 (Millipore, Milford, MA, USA). The degree of methoxylation and acetylation was determined as previously reported [ 43 ].…”
Section: Methodsmentioning
confidence: 99%